2006
DOI: 10.1111/j.0902-4441.2005.t01-1-ejh2355.x
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐term results of percutaneous vertebroplasty in multiple myeloma

Abstract: Vertebral compression fractures (VCFs) are common in multiple myeloma (MM). Percutaneous vertebroplasty (PVP) is used to stabilize vertebral collapse and treat the pain. Few studies have been carried out on PVP in MM and follow-up has tended to be short. We have prospectively evaluated the safety and efficacy of PVP in the VCFs resulting from MM or plasmacytomas. Nineteen PVP were performed in 12 consecutive patients. We monitored their pain and functional status using visual analog (VAS) and Eastern Cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 31 publications
3
23
0
1
Order By: Relevance
“…Preliminary retrospective studies have demonstrated the effectiveness of PV [16,20] and KP [21,22] in controlling pain and improving the quality of life of patients with painful MM of the spine. Few studies have prospectively analyzed the clinical outcomes achieved by PV [23] and KP [17] in relatively small series of patients. Both procedures are minimally invasive, can be performed with the patient under local anesthesia, seem to achieve the same clinical outcome [21] (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary retrospective studies have demonstrated the effectiveness of PV [16,20] and KP [21,22] in controlling pain and improving the quality of life of patients with painful MM of the spine. Few studies have prospectively analyzed the clinical outcomes achieved by PV [23] and KP [17] in relatively small series of patients. Both procedures are minimally invasive, can be performed with the patient under local anesthesia, seem to achieve the same clinical outcome [21] (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Several small studies and case series have demonstrated a beneficial effect, 1,2,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] but the largest sample size is composed of only 18 patients. Many barriers prevent the accumulation of a large patient cohort in the myeloma population, and these include reduced survival time of myeloma patients, the relative rarity of vertebroplasty treatment in myelomatous fractures, and a higher threshold of treatment criteria for patients with diffuse disease.…”
mentioning
confidence: 99%
“…The proportion of patients with good analgesic results after VP is high, ranging from 67% to 100%, while up to 70% report an improvement in active locomotion [4,9,12,[14][15][16]. The percentage of patients in the present study who reported a significant reduction of pain was as high as 92.3%.…”
Section: Discussionmentioning
confidence: 47%
“…Complications can arise from leakage of the cement outside the vertebrae. Although this occurs quite often, it does not usually result in clinically significant symptoms of compression [11,12]. Penetration of the cement into the paravertebral veins can be dangerous, however, as it may lead to the rare complication of pulmonary embolism (in 1.7% of cases).…”
Section: Discussionmentioning
confidence: 99%